Effectiveness of Transactional Communication in the Implementation of Collegiate Curriculum: A Case Study at the Christian University of Indonesia - Sihotang, Hotmaulina; Siahaan, Chontina (Advances in Social Sciences Research Journal, 2021)
The interaction between lecturers and students will be effective if delivered through transactional communication so that they can mutually encode and decode what is communicated about learning. In today’s development of the era of digital communication technology, students tend to get instant learning resources by using their gadgets instead of communicating with their lecturers. The implementation of collegiate curriculum refers to the Indonesian national qualification framework (KKNI) which will be effective with the student centered learning (SCL) approach. Lecturers act as active facilitators and students are active, mutually meaningful communication occurs so that the application of collegiate curriculum can be effectively achieved. The purpose of this study is to have description about how transactional communication is implemented in achieving learning effectiveness. The research method used is descriptive qualitative with a case study research approach. The research paradigm is constructivism. The theories used are cognitive theory and behavioral theory. The results of the research show that the implementation of the Collegiate Curriculum, namely planning, implementation, learning and learning outcomes are effective by using transactional communication